Athenian Use of Black-figure Lekythoi in Fifthcentury Burials - Brendle, Ross (Archäologischer Anzeiger, 2020)
This article re-evaluates the use and significance of funerary lekythoi in fifth-century Athens by considering in the first instance vases found in Athenian burial contexts. From the contextualized material it is clear that black-figure lekythoi remain prominent in Athenian burial practice through the first half of the fifth century. Their use then declines but does not wholly cease until the end of the century. Hastily-painted late black-figure lekythoi are by far the most common type of vase in Athenian burials throughout the fifth century and are found in simple burials and well-furnished tombs alike. The black-figure technique carried a meaning in itself, the importance of which outweighed other factors for the users of these vases.